PHYSICAL CHARACTERISTICS OF COATING FILM COMBINATION OF CORN STARCH-CHITOSAN AND THE DETERMINATION OF VITAMIN C LEVELS IN FRUIT AND VEGETABLE - I Kadek Bagiana; Bekti Nugraheni; Dyan Wigati (Jurnal Farmasi Sains dan Praktis, 2020)
Coating films is an effort to improve quality and extend the shelf life of a food ingredient. Coating film functions to coat food as well as can be consumed. The study aims to determine the best physical characteristics of the combination of corn starch-chitosan and find out the smallest % decrease in vitamin C levels from chili, tomatoes, and strawberries coated with the coating film. The materials used in this study were a combination of corn starch and chitosan 0.25%; 0.50% and 0.75%. The results showed that the coating film of 0.75% corn starch -chitosan combination has the best physical characteristics. The smallest percent decrease in vitamin C levels in chili, tomatoes, and strawberries that are dipped in coating film on a combination of corn starch-chitosan at a level of 0.75%.